E6020, a synthetic TLR4 agonist, accelerates myelin debris clearance, Schwann cell infiltration, and remyelination in the rat spinal cord. Issue 6 (2nd March 2017) - Church, Jamie S.; Milich, Lindsay M.; Lerch, Jessica K.; Popovich, Phillip G.; McTigue, Dana M.
Abstract: Oligodendrocyte progenitor cells (OPCs) are present throughout the adult brain and spinal cord and can replace oligodendrocytes lost to injury, aging, or disease. Their differentiation, however, is inhibited by myelin debris, making clearance of this debris an important step for cellular repair following demyelination. In models of peripheral nerve injury, TLR4 activation by lipopolysaccharide (LPS) promotes macrophage phagocytosis of debris. Here we tested whether the novel synthetic TLR4 agonist E6020, a Lipid A mimetic, promotes myelin debris clearance and remyelination in spinal cord white matter following lysolecithin‐induced demyelination. In vitro, E6020 induced TLR4‐dependent cytokine expression (TNFα, IL1β, IL‐6) and NF‐κB signaling, albeit at ∼10‐fold reduced potency compared to LPS. Microinjection of E6020 into the intact rat spinal cord gray/white matter border induced macrophage activation, OPC proliferation, and robust oligodendrogenesis, similar to what we described previously using an intraspinal LPS microinjection model. Finally, a single co‐injection of E6020 with lysolecithin into spinal cord white matter increased axon sparing, accelerated myelin debris clearance, enhanced Schwann cell infiltration into demyelinated lesions, and increased the number of remyelinated axons. In vitro assays confirmed that direct stimulation of macrophages by E6020 stimulates myelin phagocytosis. These data implicate TLR4 signaling in promoting repair after CNS demyelination, likely by stimulating phagocytic activity of macrophages, sparing axons, recruiting myelinating cells, and promoting remyelination. This work furthers our understanding of immune–myelin interactions and identifies a novel synthetic TLR4 agonist as a potential therapeutic avenue for white matter demyelinating conditions such as spinal cord injury and multiple sclerosis. Main Points: E6020 promotes beneficial macrophage and oligodendrocyte lineage cell responses. Macrophage TLR4 activation increases myelin uptake and degradation. Intraspinal TLR4 activation increases Schwann cell recruitment and remyelination in the CNS.